EFISIENSI TEKNIS BADAN USAHA MILIK DAERAH (BUMD) BIDANG JASA PRODUKSI PROVINSI JAWA TENGAH - Suwardi, Maskun; Prasetyo, P. Eko (Jurnal Ekonomi & Studi Pembangunan, 2018)
This research was aimed to analyze the level of technical efficiency and identify some factors that influence it and also solutions necessary to conduct to improve the efficiency of BUMD of production service field in Central Java Province. The analysis method used a Data Envelopment Analysis (DEA) by a frontier analysis approach. The BUMN analysis unit of production service field was in Central Java. Variables used were input variables (capital deposited, total expenses and employee numbers) and output variables (income, profit before tax and dividend realization). Data used was a secondary data of BUMD of production service field periods 2011-2016. The research objects covered PD. CMJT, PT. SPJT, PT. SPHC, PDAB TU and PT. PRPP. The research results showed that out of five BUMDs of production service field in Central Java Province, there were two inefficient BUMDs include PDAB TU and PT. PRPP. PDAB TU was not efficient in 2012, 2013 and 2016, while PT. PRPP was not efficient during 2011-2016. Three out of five BUMDs namely PD. CMJT, PT. SPJT and PT. SPHC achieved efficiency of 100% during research period. The BUMDs inefficiency occurred due to combining unsuitable input variable magnitude so that needed to conduct adjustment of input factor magnitude in yielding output efficiently 100%. It could be concluded that there is a trend of efficiency in BUMD of production service field every year and there are two inefficient BUMDs. The BUMD inefficiency was caused by combining disproportional input factor magnitude. It was suggested the two inefficient BUMDs should adjust input factor value magnitude in achieving output efficiently 100%